Impact of Organizational Citizenship Behavior on Managerial Effectiveness - S. A., Vivek (Prabandhan: Indian Journal of Management, 2016)
Brisk changes that occurred in various fields in the recent years have had a direct impact on almost all organizations. Environmental factors such as globalization, technology advancement, increasing importance of human resources and tough competitive conditions have necessitated the organizations’ to go through a natural process of change. Against this background, organizations inevitably need to adapt to the changing conditions. In any organization, managers need to achieve effectiveness so as to contribute towards organizational success. To find the reasons why managers are failing to achieve their effectiveness, the current study investigated the relationship between organizational citizenship behavior (OCB) and managerial effectiveness (ME) among public and private sector employees in Kerala, India. A total of 240 employees of managerial cadre were surveyed using standardized questionnaires of OCB and ME. Results indicated that the proposed relationship of OCB and ME fit the data well in Indian conditions.